Myxofibrosarcoma of the leg: A diagnostic challenge. Issue 12 (21st October 2020) - Rachdi, Imène; Daoud, Fatma; Khanchel, Fatma; Arbaoui, Ibrahim; Somai, Mehdi; Zoubeidi, Hana; Aydi, Zohra; Ben Dhaou, Besma; Debbiche, Achraf; Boussema, Fatma
Abstract: We should keep in mind slowly growing malignancies when the lesion is located close to the synovial regions of the extremities. The diagnosis of certainty of myxofibrosarcoma is histological and is based on the demonstration of the myxoid matrix, fibroblastic cells with a curvilinear arrangement of the vessels. Abstract : We should keep in mind slowly growing malignancies when the lesion is located close to the synovial regions of the extremities. The diagnosis of certainty of myxofibrosarcoma is histological and is based on the demonstration of the myxoid matrix, fibroblastic cells with a curvilinear arrangement of the vessels.